Ẕūʼn-Nurain : yaʻnī, Ḵẖalīfah-yi S̲ālis̲ Ḥaz̤rat ʻUs̲mān ibn ʻAffān ke muḵẖtaṣar va jāmiʻ ḥālāt-i zindagī - Sharar, ʻAbdulḥalīm, 1860-1926 (SAMP early 20th-century Indian books project, 1925)
On the life of ʻUthmān ibn ʻAffān, d. 656, Caliph of Islam.